Pengaruh Gaya Kepemimpinan dan Motivasi Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Industri Otomotif - Sonny Taufan (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2022)
The purpose of this study was to determine the direct and indirect effect of leadership style and work motivation variables on employee performance with job satisfaction as an intervening variable at Plaza Toyota Citereup Branch. The independent variables in this study are leadership style (X1) and work motivation (X2), the intervening variable is job satisfaction, and the dependent variable is employee performance. The population used was 42 respondents using the saturated sample method. The data analysis techniques used in this research are instrument feasibility test, path requirements test, path analysis, coefficient of determination, T test and Sobel test. The application used is SPSS version 24. The results of the T test prove that the independent variable affects the intervening variable and the dependent variable, this is evidenced by the value of t count > table. The results of the Sobel test prove that the variables of leadership style and work motivation affect employee performance through job satisfaction, as evidenced by the p-value <0.05.